Researching the obstacles of basic genetics learning in middle school students - Silva, Cirlande Cabral da (2019)
This article investigated the obstacles that high school students face when studying content related to genetic discipline. For this, we used as methodology the Grounded Theory that enabled us to elaborate an explanatory theory for the investigated phenomenon (the obstacles of the learning of genetics). Thus, we go through the three steps recommended by this Theory, which are: 1) Open Coding, which consists in naming the data (initial codes), taking into account the actions and processes of the individuals involved; 2) Axial coding, responsible for the agglutination of the initial codes in subcategories and analytical categories, and 3) Selective Codification, which consists in choosing among all the analyzed analytical categories the one with the ability to interlace all the others (central category). The Grounded Theory can be used to generate explanatory theories that, unlike the great formal theories, better explain the specific areas of empirical research since these theories emerge directly from real world data. Therefore, for this investigation, we elaborated the following Substantive Theory: "In order that the learning difficulties of the genetic concepts can be understood and overcome more easily by the students of the High School, is necessary the elaboration by the teacher of diverse strategies of teaching, through multiple theoretical-methodological approaches. Therefore, it is imperative that the genetics teacher reorient his pedagogical practice, modifying his teaching, trying to understand the complexity of the subjects, reflecting on what more appropriate way this knowledge can be transmitted so that effective learning can actually take place from the students".